Structural and thermal properties of amylose–fatty acid complexes prepared via high hydrostatic pressure. (30th October 2018) - Guo, Zebin; Jia, Xiangze; Miao, Song; Chen, Bingyan; Lu, Xu; Zheng, Baodong
Highlights: Amylose–fatty acid complexes were prepared by HHP treatment. A compact structure emerged with the formation of amylose–fatty acid complexes. High thermostability were observed in the crystal structure of complexes. Complexes exhibited V6III crystal structure and type I thermotic structure. Abstract: An innovative approach of high hydrostatic pressure was used to prepare lotus seed amylose–fatty acid complexes. The objective of this study was to investigate their structure and thermal properties. WAXD pattern of amylose changed from B-type to B- and V6 -type hybrid polymorphs, and its relative crystallinity increased upon the addition of fatty acids. Carboxyl group observed by FTIR indicates the formation of complexes. SAXS was performed to measure the lamellar structure of complexes. The complexes were more compact and had lower amounts of amorphous regions compared with amylose controls. Entrapped fatty acids, higher melting temperature, and enthalpy change of complexes but not of the controls were detected by DSC. The distribution of fatty acid molecules in the complex matrix was estimated through NMR. Under different pressures, the complexes exhibited dissimilar characteristics with the increase in aliphatic chain length, as observed by WAXD, FTIR, DSC and NMR.